On the cross road of polity, political elites and mobilization - Wejnert, Barbara; Parigi, Paolo, 1973- (Bingley : Emerald Group Publishing Limited, 2016)
This volume discusses the various interrelations that exist within and between social and political phenomena. This includes exploring the underlying social roots or origins of politics and power; the organisation, management, and process of political power structure; and the effects of political decision-making and power structures on the surrounding society and culture.
Prelims -- National identity, ethnicity, and public policy -- Political elites and political contention.
Includes bibliographical references.
Print version record
Keywords: Social Science -- Sociology -- General; Sociology; Power (Social sciences); Political sociology